Pengembangan Multimedia Interaktif Berbasis Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Kelas XI di SMA pada Materi Fluida Statis - Alfian Yosafat; Yeni Megalina (Mataram University, 2026)
Based on the results of field observations, teacher interviews, and questionnaires distributed to students, several problems were identified in the learning process. The findings revealed that learning activities were still predominantly teacher centered, resulting in low student participation during lessons and consequently leading to insufficient development of students' critical thinking skills. In addition, the use of instructional media in the learning process was still limited. Therefore, this study aims to develop an Interactive Multimedia based on the Problem-Based Learning (PBL) approach for the topic of static fluids that is valid, practical, and effective for use in physics learning, as well as capable of improving students' critical thinking skills. This study employs a Research and Development (R&D) method using the ADDIE development model. The research subjects consisted of material experts, media experts, learning experts, and 36 students of class XI F4 at SMA Negeri 1 Berastagi. The instruments used in this study included feasibility questionnaires (for material and media experts), a practicality assessment instrument (for learning experts), pretest and posttest questions, and student response questionnaires regarding the PBL-based Interactive Multimedia on static fluid material. The results showed that the developed PBL-based Interactive Multimedia on static fluid material was categorized as highly valid for use in physics learning, based on the validation results from material experts (93%) and media experts (80%). The multimedia was also categorized as highly practical based on the responses of learning experts (97%) and students (95%). Furthermore, the multimedia was proven effective, as indicated by an N-Gain score of 0.85, which falls into the high category, and an average posttest score of 86, exceeding the Minimum Learning Achievement Criteria (KKTP). Therefore, it can be concluded that the Problem-Based Learning-based Interactive Multimedia on static fluid material is valid, practical, and effective for use in learning and can improve students' critical thinking skills.